2016
DOI: 10.18063/aeb.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the extremely acidophilic archaeon Ferroplasma acidiphilum with acidophilic bacteria during pyrite bioleaching

Abstract: Bioleaching has been applied as a successful technique for metal recovery from various mineral sources like low-grade ores, waste materials and tailings. Mixed cultures of bioleaching microorganisms have a high performance in mineral dissolution. Thus far, microbial interactions in bioleaching communities are poorly understood. In this paper, the acidophilic archaeon Ferroplasma acidiphilum and the bacteria Leptospirillum ferriphilum and Sulfobacillus thermosulfidooxidans were chosen to study their interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Pure cultures of S. thermosulfidooxidans T exhibited the lowest attachment to pyrite grains, with 17% of total cells attached to pyrite after 6 h incubation (Figure 1), which coincides with previous reports [19,28]. In case of Acidianus sp.…”
Section: Pure and Mixed Culturessupporting
confidence: 91%
“…Pure cultures of S. thermosulfidooxidans T exhibited the lowest attachment to pyrite grains, with 17% of total cells attached to pyrite after 6 h incubation (Figure 1), which coincides with previous reports [19,28]. In case of Acidianus sp.…”
Section: Pure and Mixed Culturessupporting
confidence: 91%
“…Castro et al (Castro et al, 2016) showed that Sulfolobus metallicus and Acidianus copahuensis negatively influenced each other during initial attachment and pyrite dissolution, and physical contact between the two species was detected. Maulani et al (2016) found that pre-established biofilms of Leptospirillum ferriphilum inhibited the initial attachment to pyrite by cells of Ferroplasma acidiphilum and did not promote pyrite leaching by F. acidiphilum. In contrast, inactivated biofilm cells of S. thermosulfidooxidans enhanced pyrite bioleaching by F. acidiphilum.…”
Section: Introductionmentioning
confidence: 92%